2021
DOI: 10.3762/bjoc.17.103
|View full text |Cite
|
Sign up to set email alerts
|

Co-crystallization of an organic solid and a tetraaryladamantane at room temperature

Abstract: Tetraaryladamantanes have proven useful as chaperones for the co-crystallization of small molecules that do not readily crystallize by themselves. The co-crystals are often useful for structure elucidation. Usually, the small molecules are encapsulated in the crystal lattice of the aryladamantane that forms during rapid thermal crystallization. Thus far, co-crystallization has been limited to liquids as guest molecules. Here we report the co-crystal structures of phenol, which is solid at room temperature, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recently, a particularly significant method involving “crystallization chaperones” has emerged. These crystallization chaperones, including tetraaryladamantanes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and trimesic acid [ 23 , 24 , 25 , 26 ] readily form crystalline inclusion complexes with various guest molecules and provide accurate structural information on difficult-to-crystallize small molecules. Additionally, supramolecular assemblies, such as cyclodextrins [ 27 ] and pillararenes, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a particularly significant method involving “crystallization chaperones” has emerged. These crystallization chaperones, including tetraaryladamantanes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and trimesic acid [ 23 , 24 , 25 , 26 ] readily form crystalline inclusion complexes with various guest molecules and provide accurate structural information on difficult-to-crystallize small molecules. Additionally, supramolecular assemblies, such as cyclodextrins [ 27 ] and pillararenes, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Some tetraaryladamantane ethers have attracted inte­rest because of their ability to include other molecules in their crystalline lattice. 24 25 26 27 28 29 30 31 32 Building on earlier work on diaryladamantanes 17 we recently showed that 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyadamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro) are able to act as crystalline hosts for liquid compounds. This property makes them useful as crystalline coats for hazardous or reactive compounds, 30 or reversible uptake of volatile organic compounds from the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Later, substituted tetraaryladamantanes, a.k.a. “molecular chaperones”, were employed as hosts for the determination of molecular structure, including absolute configuration, for a variety of guest molecules. This method involved adding one of three different adamantoid chaperones (Figure S33) to a neat guest, in liquid form, at room temperature, heating the mixture to achieve a homogeneous solution, followed by cooling with the aim of producing a cocrystal of the adamantoid chaperone and guest. ,, Subsequently, other research groups reported the use of GS frameworks for structure determination of target molecules, , and very recently, a report in this journal described an anthracene-modified adamantoid molecular chaperone for structure determination of guests …”
mentioning
confidence: 99%
“…The typical adamantoid host protocol requires a guest to act as the solvent to dissolve the adamantoid chaperones prior to crystallization, precluding the encapsulation of solid guests. Inclusion of a solid guest was achieved by evaporation of solvent containing the chaperone and guest . Moreover, heating is required to dissolve the adamantoid chaperone (up to 150 °C), which can be problematic for thermally sensitive targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation